Factors influencing consumers’ behaviour towards fraudulent dietary supplements - Abdul Aziz, Nur Amelia Syakira; Kamarulzaman, Nitty Hirawaty (HH Publisher, 2020)
Dietary supplement fraud cases have become a major concern among consumers due to proven damage and effects on the health and lives of consumers. An increase in the risk of food safety might result from the high consumption of dietary supplements fraud. However, fraudulent activities are difficult to verify due to the lack of awareness of dietary supplements among consumers. Thus, this study was carried out to achieve the following objectives i) to determine consumers’ behaviour towards fraudulent dietary supplements and ii) to determine factors that influenced consumers’ behaviour towards fraudulent dietary supplements. A purposive sampling method was used to select 400 respondents and a structured questionnaire was established to collect the data. Descriptive analysis, Pearson correlation analysis, Chi-square analysis, factors analysis, and multiple regression analysis were the statistical analyses employed to analyze the data. The results revealed that most of the respondents were aware of fraudulent dietary supplements. Socio-demographic profiles such as age, race, religion, and education level had significant associations with consumers’ behaviour towards fraudulent dietary supplements. There was a weak positive relationship between knowledge and attitude of consumers towards fraudulent dietary supplements. Subjective norms, awareness, attitude, and perceived behavioral control were the factors that influenced consumers’ behaviour towards fraudulent dietary supplements. The study recommended that government and relevant authorities should continuously organize awareness campaigns and activities on food fraud especially for dietary supplements to ensure the consumers gained more knowledge thus, increase their awareness of fraudulent dietary supplements.